Presumptive design design provocations for innovation - Frishberg, Leo; Lambdin, Charles (MA, USA Morgan Kaufmann, imprint of Elsevier, 2016)
"Presumptive design: design provocations for innovation is for people "inventing" the future: future products, services, companies, strategies, and policies. It introduces a design-research method that shortens time to insights from months to days. Presumptive design is a fundamentally agile approach to identifying your audiences' key needs. Offering rapidly crafted artifacts, your teams collaborate with your customers to identify preferred and profitable elements of your desired outcome. Presumptive design focuses on your users' problem space, informing your business strategy, your project's early-stage definition, and your innovation pipeline. Comprising discussions of design theory with case studies and how-to's, the book offers business leadership, management and innovators the benefits of design thinking and user experience in the context of early-stage problem definition. Presumptive design is an advanced technique and quick to use." -- Provided by publisher
Chapter 1 Introducing presumptive design -- Chapter 2 PrD and design thinking -- Chapter 3 PrD and an agile way of business -- Chapter 4 Design to fail -- Chapter 5 Create, discover, analyze -- Chapter 6 Make assumptions explicit -- Chapter 7 Iterate, iterate, iterate! -- Chapter 8 The faster we go, the sooner we know -- Chapter 9 The perils of PrD -- Chapter 10 Lack of diversity -- Chapter 11 Believing our own stories -- Chapter 12 Unclear objectives -- Chapter 13 Losing our audience -- Chapter 14 Master facilitation -- Chapter 15 The creation session -- Chapter 16 The engagement session
Includes bibliographical references (pages 395-407) and index.
Keywords: Design -- Research; Design -- Social aspects